Applying the principles of governance in Directorate-General of Education in Governorate North Al Batinah in Sultanate of Oman from its employee's perspective - Al-Fathi, Khalifa Mohammed; Al-Hidabi, Dawood Abdul Malek; Al-Ani, Wajeha Thabit (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reality of applying the principles of governance in the Directorate-General of Education in North Al Batinah Governorate in Sultanate of Oman from its employee's perspective. The researcher used the quantitative approach by the descriptive and analytical method. The research tool consisted of a questionnaire distributed on three axes: disclosure, transparency, accountability, and participation. A random sample was included in the study from North Al Batinah Educational Staff, (306) employees, of whom (45) leaders and (261) employees, and the researcher used the statistical processors' program (SPSS) to deal with the data.The results of the study showed the application of governance principles in the directorate to a moderate degree, with an overall average (1.73 out of 3), at the level of major axes: The accountability axis got the highest arithmetic average (1.94), followed by the disclosure and transparency axis with an average (1.80), both of which have an application degree (medium), and finally, the participation axis got an application score (low) with a mean (1.40). The results also showed statistically significant differences in favor of leaders in the disclosure axis, transparency, while no differences appeared in the axes' rest. The study recommends the need to spread the culture of governance among North Al Batinah Governorate employees and enhance the administrative system with the integration of electronic work mechanisms that ensure ease of disclosure and transparent application of the rules and laws of accountability of all without exception. The study also recommends activating the control mechanisms and freedom of expression to ensure the right of participation for the directorate's employees in policy and decision making.
Keywords: Principles of Governance; General Directorate of Education; North Al Batinah Governorate